Cell Division Patterns in the Peristomial Layers of the Moss Genus Costesia: Two Hypotheses and a Third Solution - Ignatov, Michael S.; Spirina, Ulyana N.; Kolesnikova, Maria A.; Larraín, Juan; Ignatova, Elena A. (Frontiers in Plant Science, 2020)
The Chilean endemic genus Costesia belongs to the Gigaspermaceae, one of the most basal groups of arthrodontous mosses. While none of the species in this family has a peristome, earlier stages of sporophyte development often disclose its basic structure. The study of Costesia sporophytes at the early stages of development was conducted to identify possible similarities with Diphyscium, the genus sister to Gigaspermaceae plus all other arthrodontous mosses in the moss phylogenetic tree. Diphyscium shares a strongly unequal cell division pattern with the Dicranidae. In groups more closely related to Diphyscium, as it is the case of Costesia, this pattern is not known. Our study of Costesia found only irregular presence of slightly unequal cell divisions that may then be considered as a plesiomorphic state in peristomate mosses. The most frequently present pattern revealed in Costesia is common with the Polytrichaceae, a more basal moss group with nematodontous peristomes.